INVESTIGATING THE MECHANISM OF ASP IN OIL-WATER INTERFACE BY MOLECULAR DYNAMICS - NUMIN, MOHD SOFI (2021)
Chemical injection such as alkaline (A), surfactant (S) and polymer (P) in Chemical Enhanced Oil Recovery (CEOR) can improve oil recovery by modifying the injected fluid characteristics to enhance interaction with oil in the reservoir. The presence of complex composition in CEOR flooding complicates the study in investigating the mechanism of ASP in the oil-water interface. For this reason, the rheological properties and interfacial tension (IFT) reduction mechanism of the ASP solution with the presence of the crude oil were investigated experimentally and by molecular dynamics (MD) simulation. In rheological properties analysis, five different concentrations of ASP and SP emulsions were tested, and 20 water cuts (WC) ASP solution showed an excellent performance with better shear properties, viscoelasticity, and stable emulsion viscosity at 60% of crude oil. The IFT analysis was then conducted to determine the optimum ASP composition in reducing the IFT value. The spinning drop video tensiometer (SVT) instrument was used to measure the IFT value experimentally, and the optimum composition of ASP in reducing the IFT value was 0.3 M S672, 1.0 M Na2CO3, and 1000 ppm hydrolyzed polyacrylamide (HPAM) solution with the IFT value of 0.08 mN/m. The MD simulation successfully investigated the mechanism of ASP in reducing the IFT value. The mechanism in IFT reduction was explained by the surfactant adsorption at the interface, interfacial thickness, hydrogen bond formation, and RDF analysis between surfactant headgroups with water molecules at the system's interface. The high in-depth study such as rheological properties analysis and MD simulation technique explained the ability of the ASP systems in oil recovery before being used in the field. This method is very beneficial for further exploration of ASP formulation and developing new chemicals, thus reducing the chemicals usage.